(untitled) (Research, Society and Development, 2022)
Purpose: To identify the knowledge acquired by caregivers of children/adolescents with type 1 Diabetes Mellitus (DM1) in health education consultations and its implication in home care, as well as to evaluate the performance of the multidisciplinary team in the transmission of this knowledge. Methodology: Descriptive study with a qualitative approach carried out remotely with the companions of children/adolescents with DM1 who are followed up at an outpatient clinic specializing in endocrinology at a University Hospital in the Federal District. For data collection, a participant characterization form was used and an individual non-directive interview was conducted. Data collection was carried out through telephone contact and video conference. Results: Five caregivers participated in the study, aged between 36 and 47 years. The sample was delimited by data saturation. In this study, it was revealed that knowledge related to food, physical activity and rights to inputs proved to be adequate, although the sample has small gaps in knowledge about medications and in the use of new technologies. Health education by the multidisciplinary team proved to be a fundamental factor for good insulin management, regardless of the previous technical skills of caregivers and patients, although it is not the only source of information, and the internet is also widely used. Conclusion: Considering the knowledge, difficulties and needs of the individual related to the disease is essential for the effective performance of professionals in the health education process, aiming to equip the caregiver for effective adherence to the treatment of children with DM1.